2019
DOI: 10.1186/s12889-019-6825-y
|View full text |Cite
|
Sign up to set email alerts
|

Does unemployment contribute to poorer health-related quality of life among Swedish adults?

Abstract: Background Previous studies have shown that unemployment has negative impacts on various aspects of health. However, little is known about the effect of unemployment on health-related quality of life. Our aim was to examine how unemployment impacts upon health-related quality of life among Swedish adults, and to investigate these effects on population subgroups defined by education level, marital status, previous health, and gender. Methods As part of a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
87
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 27 publications
11
87
1
3
Order By: Relevance
“…This concluded that unemployment is associated with poor HRQOL. This is consistent with several reports that unemployed people more possible to have poorer HRQOL than the employed [20,25,40] . Specifically, it may be due to the fact that people experienced unemployment are deprived of these benefits (e.g.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This concluded that unemployment is associated with poor HRQOL. This is consistent with several reports that unemployed people more possible to have poorer HRQOL than the employed [20,25,40] . Specifically, it may be due to the fact that people experienced unemployment are deprived of these benefits (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…It is with great consequence to prevent the unemployed from falling into long-term health and poverty, to improve the precise poverty alleviation policy and to promote the construction of healthy China. Despite many health measurement being used to assess the effect of unemployment on health, there is still not much knowledge about health-related quality of life [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Despite potential cultural differences in preferences for health states between the German and the British population, we believe that the British value set is more useful to value health states in our sample. Additionally, we want to point out that using the British value set in a non-UK-based study is a frequently implemented approach [46][47][48][49].…”
Section: Measurement Of Effects: Eq-5d-3l and Qalymentioning
confidence: 99%
“…Employability and professional status are relevant factors in well-being and quality of life (Norström et al, 2019;Thern et al, 2017;Vancea & Utzet, 2016). However, research on the social educators' professional situation and employability is scarce, and no study on this subject has been found in Portugal.…”
Section: Problem Statementmentioning
confidence: 99%
“…In this sense, Bernston and Maklund (2007) found an association between perceived employability, general health and mental well-being. Unemployment and precariousness, on the other hand, seem to be associated with risk behaviors, lower quality of life rates and increased risks for mental health, like anxiety, depression and feelings of hopelessness and worthlessness (Norström et al, 2019;Thern et al, 2017;Vancea & Utzet, 2016). Therefore, unemployment and precariousness appear as important public health problems (Norström et al, 2019;Vancea & Utzet, 2016).…”
Section: Introductionmentioning
confidence: 99%